Auxin‐mediated Aux/IAA‐ARF‐HB signaling cascade regulates secondary xylem development in Populus. Issue 2 (1st February 2019) - Xu, Changzheng; Shen, Yun; He, Fu; Fu, Xiaokang; Yu, Hong; Lu, Wanxiang; Li, Yongli; Li, Chaofeng; Fan, Di; Wang, Hua Cassan; Luo, Keming
Summary: Wood development is strictly regulated by various phytohormones and auxin plays a central regulatory role in this process. However, how the auxin signaling is transducted in developing secondary xylem during wood formation in tree species remains unclear. Here, we identified an Aux/INDOLE‐3‐ACETIC ACID 9 (IAA9)‐AUXIN RESPONSE FACTOR 5 (ARF5) module in Populus tomentosa as a key mediator of auxin signaling to control early developing xylem development. PtoIAA9, a canonical Aux / IAA gene, is predominantly expressed in vascular cambium and developing secondary xylem and induced by exogenous auxin. Overexpression of PtoIAA9m encoding a stabilized IAA9 protein significantly represses secondary xylem development in transgenic poplar. We further showed that PtoIAA9 interacts with PtoARF5 homologs via the C‐terminal III/IV domains. The truncated PtoARF5.1 protein without the III/IV domains rescued defective phenotypes caused by PtoIAA9m . Expression analysis showed that the PtoIAA9‐PtoARF5 module regulated the expression of genes associated with secondary vascular development in PtoIAA9m ‐ and PtoARF5.1 ‐overexpressing plants. Furthermore, PtoARF5.1 could bind to the promoters of two Class III homeodomain‐leucine zipper (HD‐ZIP III) genes, PtoHB7 and PtoHB8, to modulate secondary xylem formation. Taken together, our results suggest that the Aux/IAA9‐ARF5 module is required for auxin signaling to regulate wood formation via orchestrating the expression of HD‐ZIP III transcription factors in poplar.